SURVEI BERBAGAI JENIS KETERAMPILAN YANG DIBUTUHKAN DESA BINAAN DALAM MEMPERSIAPKAN KEGIATAN PKM HIBAH DIKTI - Suhartono; Sidik, Syahrial; A. Maolani, Rukaesih (Premium Insurance Business Journal, 2023)
The purpose of this research was conducted to obtain data/information about what problems exist in research locations that require assistance through PKM activities for lecturers and students. This is done to meet the requirements for obtaining PKM funds through Dikti grants. The study used a survey method conducted in Sukaratu village, Banyuresmi sub-district, Garut district with 25 respondents by filling out a questionnaire. From the results of filling out the questionnaire it was concluded that: 1) the community needs skills education for teenagers; 2) skills education for housewives; 3) skills for the head of the household in marketing their agricultural products. Suggestions from elders from the research area needed assistance to make the Sukaratu assisted village area a fruit-producing center.